Assessment of the clinicopathological relevance of mesothelin level in plasma, peritoneal fluid, and tumor tissue of epithelial ovarian cancer patients. Issue 10 (October 2018) - Okła, Karolina; Surówka, Justyna; Frąszczak, Karolina; Czerwonka, Arkadiusz; Kaławaj, Katarzyna; Wawruszak, Anna; Kotarski, Jan; Wertel, Iwona
Ovarian cancer remains the most lethal gynecologic malignancy. This is due to lack of effective screening, diagnosis predominance in late stage of disease, a high recurrence rate after primary therapy, and poor treatment response in platinum-resistant tumor. Thus, unique biomarkers, predictive of individual disease course, and prognosis are urgently needed. The aim of our study was to assess the clinicopathological significance of plasma, peritoneal fluid, and tumor tissue levels of mesothelin in epithelial ovarian cancer patients. Plasma and peritoneal fluid levels of mesothelin were measured by enzyme-linked immunosorbent assay. Tissue expression of MSLN was evaluated using quantitative real-time polymerase chain reaction. Preoperative plasma mesothelin levels were significantly higher in epithelial ovarian cancer patients in comparison to the patients with benign tumor and controls. There have been noticed significant differences in the plasma mesothelin levels based on International Federation of Gynecology and Obstetrics stage, grade, and histology type. No significant changes were observed between Kurman and Shih type I versus type II epithelial ovarian cancer. Interestingly, peritoneal fluid mesothelin levels revealed significant differences based on both grade and Kurman and Shih–type epithelial ovarian cancer. There were no relevant changes in the mesothelin level in peritoneal fluid between different stages and histology types compared to benign tumor. MSLN expression level in tumor tissue was significantly higher based on stage, grade, and Kurman and Shih–type epithelial ovarian cancer than in the benign masses. In addition, data showed significant higher MSLN expression in endometrioid tumors compared to benign masses and serous tumors. Plasma, peritoneal fluid, and tumor tissue levels of mesothelin positively correlated with level of CA125. Low mesothelin concentrations in plasma were also associated with prolonged patient survival. More importantly, we revealed that plasma mesothelin level was correlated with both peritoneal fluid mesothelin level and tumor MSLN expression. This study highlights that plasma mesothelin level may be a useful noninvasive biomarker surrogate for local tumor mesothelin status in monitoring of epithelial ovarian cancer patients.